Comparative meta-analysis of balloon-expandable and self-expandable valves for transcatheter aortic valve replacement. (15th October 2015) - Agarwal, Shikhar; Parashar, Akhil; Kumbhani, Dharam J.; Svensson, Lars G.; Krishnaswamy, Amar; Tuzcu, E. Murat; Kapadia, Samir R.
Abstract: Background: Balloon-expandable valves (BEVs) and self-expandable valves (SEVs) are two major types of valves utilized for transcatheter aortic valve replacement (TAVR). We conducted a meta-analysis of available studies to compare the safety and efficacy of these two valve types. Methods: Medline search was conducted using standard search terms to determine eligible studies. Primary outcomes of the meta-analysis included death and stroke at 30 days and 1 year. Pooled estimates of procedural outcomes were also compared between the valve types. Analysis was performed for entire cohort and separately for patients undergoing transfemoral TAVR (TF-TAVR). Results: Analysis of entire cohort revealed similar 30-day mortality in the SEV and BEV cohorts. There was no significant difference in the incidence of stroke at 30 days between the two study groups. Both pooled comparisons demonstrated a significant heterogeneity with I 2  > 50%, necessitating the use of random effect modeling. We observed a significantly higher incidence of new pacemaker implantation, aortic regurgitation ≥ 2 + at 30 days, valve embolization, and need for > 1 valve following SEV implantation compared with BEV implantation. Analysis of TF-TAVR cohort showed higher 30 day [IRR (95% CI): 1.34 (1.19–1.52)] but a similar 1-year mortality [IRR (95% CI): 1.07 (0.96–1.19)] for SEV compared to BEV implantation. Conclusion: Compared to BEV implantation, SEV implantation was associated with a similar risk of mortality and stroke at 30-day and 1-year follow-up duration. Analysis of the TF-TAVR cohort revealed a significantly higher mortality at 30 days among patients undergoing SEV implantation, compared with BEV implantation. In addition, there was a significantly higher incidence of other adverse events noted above, following SEV implantation, compared with BEV implantation.